A novel evaluation model of user acceptance of software technology in healthcare sector - Mohamadali, Noor Azizah (2010)
Effective evaluation of healthcare information systems is necessary in order to ensure systems adequately meet the requirements and information processing needs of the users and healthcare organisations. A number of studies have proposed evaluation frameworks to aid in evaluation work. However, some of them can be improved upon. This paper proposes a novel evaluation model to evaluate user acceptance of software technology within the healthcare sector. It describes the theoretical basis behind the development of the research model and methodology being employed to validate the model.